2007
DOI: 10.1677/erc-06-0030
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the S-phase kinase-associated protein 2 in thyroid cancer

Abstract: Loss of expression of the cyclin-dependent kinase inhibitor p27 through enhanced protein degradation frequently occurs in human cancer. Degradation of p27 requires ubiquitination by the S-phase kinase-associated protein 2 (Skp2), a member of the F-box family of Skp1-Cullin-F-box protein ubiquitin ligases. In the present study, we have investigated the role of Skp2 in human thyroid tumours. Immunohistochemistry analysis showed that Skp2 was overexpressed significantly in thyroid carcinomas (26 out of 51) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
3
23
0
1
Order By: Relevance
“…SKP2 was inversely associated with p27Kip1 protein levels (40). We therefore determined the role of both SKP2 and p27Kip1 as prognostic markers and found that those CRC that exhibit deregulation of SKP2 and p27Kip1, i.e., high level of SKP2 and low level of p27Kip1, have decreased overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…SKP2 was inversely associated with p27Kip1 protein levels (40). We therefore determined the role of both SKP2 and p27Kip1 as prognostic markers and found that those CRC that exhibit deregulation of SKP2 and p27Kip1, i.e., high level of SKP2 and low level of p27Kip1, have decreased overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…MSTO-211H, REN and MET-5A cells were stably transduced with lentiviral vectors expressing a set of five short hairpin RNAs (shRNAs) against CDKN1B transcript (Mission shRNA, Sigma-Aldrich) and the non-target control (Mission non-target control, Sigma-Aldrich). Lentiviral vector preparation and infection was performed as previously described (Chiappetta et al, 2007). The effect of SRC inhibition on cell viability and caspase-3 activity was evaluated in MSTO-211H, REN and MET-5A cells expressing p27 and not expressing p27 after treatment of these cell lines with 7.5 mM SI83 and SI91 for 72 h. Before performing caspase-3 assay, cells were counted with trypan blue and the obtained data were used to evaluate cell viability.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Therefore, alternative mechanisms that act at the posttranscriptional or post-translational level have been suggested. These alternative mechanisms include a lower translation rate of CDKN1B mRNA (19), an increase in protein degradation (20,21), and the cytosolic mislocalization of p27 protein (22,23,24).…”
Section: Introductionmentioning
confidence: 99%